The Effects of Pre-announced Consumption Tax Reforms on the Sales and Prices of Consumer Durables - Thiess Büttner; Boryana Madzharova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper utilizes a unique micro data set on consumer durables to study the effect of consumption tax reforms on the time path of consumption. The dataset reports the monthly sales of individual products and their consumer prices in 22 European countries, which enacted numerous consumption tax reforms in recent years. We implement a reduced form specification for sales that allows us to test theoretical predictions by a standard inter-temporal model of consumer choice under different assumptions about the pass-through of taxes into prices. Our identification strategy exploits the trading of individual products in multiple countries. The results document that changes in baseline consumption tax rates are fully and quickly shifted into consumer prices and exert very strong effects on the time path of consumption. We find that a one percentage point increase in consumption taxes causes an inter-temporal shift in consumption by 3 or more percent. In addition, purchases of durable goods increase temporarily by about 2 percent in the last month before a tax increase.
Keywords: D15; D12; H24; H32; E21; E62; 330; Tax Reform; Fiscal Policy; Consumption Tax; Pass-Through; Tax Incidence; Durable Goods